Impacto del turismo en el catastro de establecimientos turísticos del cantón Ventanas, año 2021 - Peralta Meléndez, Angie Liz (2021)
The objective of this research project is to analyse the impact of tourism on the cadaster of tourist establishments in the canton of Ventanas, for which bibliographical sources were consulted on the subject such as Movimientos Internos: GEOVIT. First Geo portal of Internal Tourist Trips of Ecuador and the Ministry of Tourism: MINTUR. The analysis process has shown that, in the last 3 years, the establishments that have been registered in the different sectors such as Accommodation, Transport and Food, the results have varied according to the latest update. At the same time, the most prevalent sector of business is commerce and services, and the present investigation has a practical influence with a methodology of observational analysis. The analysis method is used for the collection of relevant information and data to help with the problematic indicators of the impact of tourism. The main objective is to capture impressions on the development projections of the tourism sector in terms of economic and employment stability losses, the search for incentives and possible reactivation strategies.